Sustainability of agricultural and livestock production systems - Hinojosa Benavides, René Antonio (2019)
The aim was to analyze concepts related to the sustainability of agricultural production systems, reflected in their ecological, social and economic dimensions. Sustainability reflects sustainable economic prosperity over time with quality of life, while protecting the natural systems of the planet. It was concluded that sustainable development frames the capacity that human has developed to meet the needs of present generations without compromising opportunities for the development of future generations and agricultural activity is an ecological problem, so it is necessary to evaluate the efficiency of their systems in relation to their sustainability.